Optimalisasi Pelaksanaan Program Kerja KKN Dalam Bacaan Qur’an Metode Talaqqi Terhadap Kecerdasan Anak-Anak Desa Pulau Panggung - Muhammad Khozi Rahman Hakim; Epa Perawati; Nadiah Gita Ananda; Iqbal Gumasa; Viola Junia Vitaloka; Mita Riyani; Hidayana Asi Saripa Pikri; Husnun Afifa; Deby Liyana Putri Utami; Masrifah Hidayani (Lembaga Pengembangan Kinerja Dosen, 2024)
In the fast-paced era of globalization, the role of youth is crucial in preserving and developing religious values in society. In Pulau Panggung Village, despite having significant youth potential, their participation in religious activities remains low. This has led to a decline in understanding and practicing religious values, especially among children. To address this issue, the implementation of the Community Service Program (KKN) focusing on Quranic reading and writing education using the Talaqqi method can provide a solution. The Talaqqi method, which involves direct interaction between the teacher and students, offers in-depth personal guidance in Quranic education. It is expected to enhance children's skills in reading and writing the Quran and their understanding of religious values. Additionally, the program aims to boost religious enthusiasm among youth through comprehensive education about religion and culture. By optimizing the implementation of this KKN program, it is hoped that youth involvement in religious activities will improve and religious values in society will be strengthened.